Cryptic diversity within Nyctixalus (Anura: Rhacophoridae): a new species, a resurrection, and a redescription - Dever, Jennifer A.; Mcguire, Jimmy A.; Iskandar, Djoko T.; Hamidy, Amir; Grismer, L. Lee (Zootaxa, 2026)
The examination of molecular markers confirms hidden diversity and reveals a new species within the Nyctixalus pictus (Peters, 1871) complex. Three genetically distinct clades were recovered: one from the Thai-Malay Peninsula; one from Sumatra, Indonesia; and one from Sarawak, Borneo, East Malaysia. Voucher specimens from each region were compared, and significantly different mean values were found through morphological analyses. The populations also differ significantly in morphospace, as determined by PCA, DAPC, and MFA analyses. The Thai-Malay Peninsula individuals have a distinct, rounded and slightly elongated snout shape compared to the other two clades. Based on these combined data, these three clades are recognized as distinct species. The name N. anodon is reinstated for those from Sumatra, Indonesia. The type locality of Sarawak, East Malaysia for N. pictus restricts the distribution of the species to Borneo. The type specimen of N. pictus was lost (pers. communication, G. Doria), and no lectotype or syntypes were described; thus, a specimen from Sarawak, Borneo, in the collection of the Field Museum of Natural History, Chicago (FMNH), is designated here as the neotype of N. pictus.